"The Most Important Dress in the Country": The Rhetoric of Glamour in the Smithsonian's "The First Ladies". Issue 3 (3rd July 2017) - Keohane, Jennifer
ABSTRACT: This article examines the exhibit "The First Ladies" in the Smithsonian's National Museum of American History. The exhibit, composed primarily of inauguration gowns and china settings from state dinners, has existed since the early twentieth century and is one of the Smithsonian's most popular and controversial exhibits. I argue that "The First Ladies" relies on a rhetoric of glamour that emphasizes the perfection, ease, and mystery of those who hold this role. This rhetoric constructs a subjectivity for viewers as spectators appreciative of the elite culture on display that perpetuates a masculine way of seeing. The overall impact depoliticizes and domesticates the role of first lady, sidestepping questions of female political power while locating women in a benign, domestic realm. This article contributes to our understanding of how glamour invites us to understand the public memory of powerful women.